FUNGSI BADAN PENGAWAS KEUANGAN DAN PEMBANGUNAN (BPKP) BERDASARKAN PERATURAN PRESIDEN NOMOR 192 TAHUN 2014 - Fitri Irawan, Nadia; Syarif, Afif (Fakultas Hukum Universitas Jambi, 2021)
Results of the Authority of the Financial and Development Supervisory Agency Based on Presidential Regulation Number 192 of 2014 concerning the Financial and Development Supervisory Agency. Supervision of the planning and implementation of programs and/or activities that may hinder the smooth development, audits of price adjustments, audits of claims, audits of investigations on cases of irregularities indicating financial loss to the state/region, audits of calculating state/regional financial losses, providing expert information and efforts to prevent corruption. Whereas to carry out the supervisory function as stated in Article 3 letter e, in accordance with Article 27 of the Presidential Regulation Number 192 of 2014 it is carried out through the Deputy for Investigation of the BPKP. which reads that the Deputy for Investigation carries out the task of assisting in the field of monitoring the smooth running of development including cross-sectoral programs, prevention of corruption, audits of price adjustments, audits of claims, investigative audits of cases of irregularities with indications of harming state finances, audits of calculating state financial losses and giving expert testimony. Mechanism of the Financial and Development Supervisory Agency (BPKP) Determines State Financial Losses Based on Presidential Regulation Number 192 of 2014 concerning BPKP. The authority of BPKP in laws and regulations is based on the function of BPKP as stated in Article 3 letter e, then BPKP is an institution authorized to calculate (assess) state financial losses, In particular, BPKP is also authorized to assess state financial losses in an effort to prevent corruption because BPKP is also authorized to conduct investigative audits on cases that are indicated to be detrimental to state finances (corruption), When reviewing the source of authority owned by BPKP, then the authority possessed by BPKP is included in the delegative authorit.